Serum Uric Acid Levels and Risk of Eight Site-Specific Cancers: A Mendelian Randomization Study - Jiang, Minxiao; Ren, Liangliang; Chen, Songzan; Li, Gonghui (Frontiers in Genetics, 2021)
The relationship between serum uric acid levels and cancer risk remains controversial. Here, a two-sample Mendelian randomization analysis was performed to identify a causal effect of serum UA levels on cancer risk. Twenty-six single nucleotide polymorphisms strongly associated with serum UA levels were screened as genetic variants from large-scale meta-analysis data of a genome-wide association study of 110,347 European individuals. Genetic associations with eight common site-specific cancers were subsequently explored. A total of six Mendelian randomization methods were used to estimate the potential effect of serum UA levels on cancer risk, including random effects inverse variance weighting, fix effects inverse variance weighting, MR-Egger, median weighting, mode weighting and simple mode analysis. Our primary random effects inverse variance weighted analysis revealed that no significant associations with cancers was found (all p > 0.05). And sensitivity analyses and additional analyses also showed similar pooled results. In conclusion, no significant causality between serum UA levels and cancer risk was evidenced.